2022
DOI: 10.1002/gch2.202100091
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanomaterials and Ionic Zn Partition within Wastewater Sludge Investigated by Isotopic Labeling

Abstract: The increasing commercial use of engineered zinc oxide nanomaterials necessitates a thorough understanding of their behavior following their release into wastewater. Herein, the fates of zinc oxide nanoparticles (ZnO NPs) and ionic Zn in a real primary sludge collected from a municipal wastewater system are studied via stable isotope tracing at an environmentally relevant spiking concentration of 15.2 µg g−1. Due to rapid dissolution, nanoparticulate ZnO does not impart particle‐specific effects, and the Zn io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, ZnO ENMs dissolution could also play a significant role in the nanomaterials’ fate, especially when incubated in more acidic environmental media such as wastewater and sludge. [ 39 ] Bian et al [ 40 ] indicated that there is a size‐dependent dissolution behaviour with the smallest ZnO nanoparticles showing a greater propensity for dissolution, hence the proven ZnO aggregation occurring during the aging and incubation procedures may have mitigated this conduct. In addition, ENMs/aggregates of different shapes (i.e., faceted, fibers, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ZnO ENMs dissolution could also play a significant role in the nanomaterials’ fate, especially when incubated in more acidic environmental media such as wastewater and sludge. [ 39 ] Bian et al [ 40 ] indicated that there is a size‐dependent dissolution behaviour with the smallest ZnO nanoparticles showing a greater propensity for dissolution, hence the proven ZnO aggregation occurring during the aging and incubation procedures may have mitigated this conduct. In addition, ENMs/aggregates of different shapes (i.e., faceted, fibers, etc.)…”
Section: Discussionmentioning
confidence: 99%